2015
DOI: 10.1227/neu.0000000000000595
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clinical Implications of Carotid Branch Occlusion Following Treatment of Internal Carotid Artery Aneurysms With the Pipeline Embolization Device

Abstract: The incidence of major supraclinoid ICA branch occlusion after treatment with PEDs was low. These events were not associated with new neurological deficits nor were they related to the number of PEDs deployed or the origin of ICA branches from the aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 16 publications
3
43
0
Order By: Relevance
“…12,42,75 Mortality rates ranged from 0% to 4.6% and 0% to 20% in ruptured cases. 51,75 Major concerns with coiling are coil prolapse into the parent vessel and coil penetration, which is estimated to be 2.5%. 72 Procedurerelated complications were comparable in the SAC group and the coiling-alone group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,42,75 Mortality rates ranged from 0% to 4.6% and 0% to 20% in ruptured cases. 51,75 Major concerns with coiling are coil prolapse into the parent vessel and coil penetration, which is estimated to be 2.5%. 72 Procedurerelated complications were comparable in the SAC group and the coiling-alone group.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the complications in the series were asymptomatic, and permanent morbidity rates ranged between 0% and 10%. 60,65,70,71,75 However, SAC of acutely ruptured aneurysms is associated with significantly higher complication rates (5%-25% vs 0%-16%) than unruptured aneurysms. 12,42,75 Mortality rates ranged from 0% to 4.6% and 0% to 20% in ruptured cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study, of 49 patients with 68 carotid aneurysms, found an overall branch occlusion rate of 4.4% (4% of ophthalmic and 7.1% of posterior communicating arteries) without clinical sequelae at follow-up angiography. 9 A study of 11 patients with 13 carotid aneurysms in which the posterior communicating artery ostium was covered by one or more FDSs found an occlusion rate of 27%, with an additional 18% with diminished flow. 10 Finally, 2 reports with a combined total of 43 anterior choroidal arteries spanned by at least 1 FDS in the treatment of carotid aneurysms documented 2 branch occlusions (4.7%) at follow-up, without clinical sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…10) Several studies indicated that PED insertion at the origin of the ophthalmic artery did not frequently cause occlusion of the ophthalmic artery or clinical ocular symptoms. 15,16) On the other hand, a study reported that detailed ophthalmological examination of 28 patients in whom the PED was inserted showed ophthalmological complications in 39.3% even in the absence of signs; caution is needed. 17) With respect to changes in stent morphology after FRED insertion, Kocer et al reported stent foreshortening the day after treatment in one patient.…”
Section: Resultsmentioning
confidence: 99%